Solidarity in Fandom: An Analysis of Weeaboo Community Prosocial Behavior - Ellia, Seth Kenan; Susanto, Timotius Iwan (Psikoborneo: Jurnal Ilmiah Psikologi, 2026)
The weeaboo community, referring to enthusiasts of Japanese popular culture in Indonesia, represents a large subcultural group that is frequently stigmatized as “no life” (nolep) or antisocial. The paradox between such stigma and the community’s strong internal solidarity provides the foundation for this study. This research aimed to examine the dynamics of prosocial behavior within the wibu community as an empirical counter-narrative to sociocultural stigmatization. A descriptive quantitative approach was employed using a mini-survey of 42 Generation Z participants aged 18–25 years, selected through purposive sampling. Data were collected using the Indonesian adaptation of the Prosocialness Scale for Adults (PSA) by Sefianmi et al. (2023), which assesses the dimensions of sharing, helping, care taking, and empathy. The findings revealed that the weeaboo community demonstrated a moderate level of prosocial behavior (M = 42.76). The highest mean scores were observed in Helping (M = 11.69) and Sharing (M = 11.33). These results challenge the stereotype of antisocial behavior by indicating that experiences of marginalization may strengthen in-group cohesion and solidarity as forms of emotional support. Drawing on Bronfenbrenner’s Ecological Systems Theory and the Rejection-Identification Model, these prosocial behaviors can be understood as socio-psychological adaptations emerging through interactions within the microsystem, reinforced by the mesosystem, and transformed into collective resilience in response to macrosystem pressures. Overall, the findings suggest that subcultural affiliation does not diminish social concern but may instead foster social capital, highlighting the need to deconstruct stigma toward fan communities.Komunitas wibu, yaitu penggemar budaya populer Jepang di Indonesia, merupakan kelompok yang cukup besar, tetapi masih sering menghadapi stigma sosial berupa pelabelan “nolep” (no life) atau antisosial. Paradoks antara stigma tersebut dan kuatnya solidaritas internal menjadi dasar penelitian ini. Penelitian bertujuan menganalisis dinamika perilaku prososial pada komunitas wibu sebagai kontra narasi berbasis data empiris terhadap stigmatisasi sosiokultural. Penelitian menggunakan pendekatan kuantitatif deskriptif melalui mini survey terhadap 42 partisipan Generasi Z berusia 18–25 tahun dengan teknik purposive sampling. Pengumpulan data dilakukan menggunakan adaptasi Prosocialness Scale for Adults (PSA) versi Bahasa Indonesia oleh Sefianmi et al. (2023) yang mengukur dimensi sharing, helping, care taking, dan empathy. Hasil penelitian menunjukkan bahwa komunitas wibu memiliki tingkat perilaku prososial pada kategori moderat (M = 42,76). Dimensi dengan skor tertinggi adalah Helping (M = 11,69) dan Sharing (M = 11,33). Temuan ini membantah stereotip antisosial dengan menunjukkan bahwa pengalaman marginalisasi justru dapat memperkuat kohesi dan solidaritas in-group sebagai bentuk dukungan emosional. Berdasarkan Teori Ekologi Bronfenbrenner dan Rejection Identification Model, perilaku prososial tersebut merupakan bentuk adaptasi sosiopsikologis yang berkembang dari interaksi pada tingkat mikrosistem, diperkuat melalui mesosistem, dan menjadi resiliensi kolektif dalam menghadapi tekanan makrosistem. Temuan ini menunjukkan bahwa afiliasi subkultural tidak mengurangi kepedulian sosial, melainkan dapat menjadi sumber terbentuknya modal sosial yang mendorong perlunya dekonstruksi stigma terhadap komunitas penggemar.